Modified Dismembered Technique of Laparoscopic Transperitoneal Pyeloplasty in Children - Mostafa Zain*; Sameh Shehata; Ahmed Khairi; Mohamed El-Sawaf; Mohamed Abouheba (SVU - International Journal of Medical Sciences, 2023)
Background: Laparoscopic pyeloplasty in children gained more and more popularity over the past two decades. However, it remains technically challenging with the most steps of the procedure are ureteric spatulation, DJ insertion, and intracorporeal anastomosis. Many modifications have been proposed to address these issues. In this article, we present our surgical approach to laparoscopic transperitoneal modified dismembered pyeloplasty highlighting some tips to make it easy. Objectives: This study was conducted to evaluate the outcomes of laparoscopic management of ureteropelvic junction obstruction children. Patients and Methods: This was a prospective study carried out on patients who presented with UPJO to our center from May 2019 to October 2021. All the cases underwent laparoscopic transperitoneal modified dismembered pyeloplasty where complete dismembering is deferred after the ureteropelvic anastomosis to prevent ureteral torsion and to use the redundant pelvis as a handle for ureteric manipulation. We used 3 simple techniques for antegrade insertion of DJ. Results: The study included 25 patients (19 males and 6 females) The mean age at operation was 30.88 ± 27.48 months. The mean time needed for the anastomosis was 80 minutes while the mean total operative time was 155 minutes. No conversion was needed. Apart from 2 cases, all other patients showed significant improvement of the degree of hydronephrosis and renal split function. Conclusion: The described modifications facilitated performing the procedure rendering laparoscopic pyeloplasty to be a less demanding and much easier procedure than the conventional technique.